Whole-genome analysis revealed the growth-promoting mechanism of endophytic bacterial strain Q2H1 in potato plants - Wang, Yuhu; Zhao, Qianqian; Sun, Zhenqi; Li, Yahui; He, Hongtao; Zhang, Yuanyu; Yang, Xiangdong; Wang, Dong; Dong, Baozhu; Zhou, Hongyou; Zhao, Mingmin; Zheng, Hongli (Frontiers in Microbiology, 2022)
Endophytes are nonpathogenic inhabitants of healthy plant tissues and have been found to promote plant growth and health. The endophytic bacterial strain Q2H1 was isolated from the roots of potatoes and was identified to exhibit growth-promoting effects in potato plants. Whole-genome sequencing was performed to reveal the mechanism underlying its growth-promoting effect. The obtained sequencing data of approximately 5.65 MB encompassed 5533 Coding sequences.. Nine secondary metabolite gene clusters, including siderophore gene clusters closely associated with plant growth promotion were predicted by antiSMASH software. Comparative genomic analysis revealed that Q2H1 belongs to the genus Peribacillus. By gene function annotation, those genes related to plant growth-promoting (PGP) activities, including the indole-3-acetic acid (IAA) synthesis in tryptophan metabolism, siderophore biosynthetic activity, phosphate solubilization, nitrogen fixation, and related genes, were summarized. IAA (14.4 μg/mL) was presumptively produced by Q2H1 using the Salkowski colorimetric method. Five genes, namely, phoU, pstB, pstA1, pstC, and pstS, were annotated for phosphate solubilization, which is associated with the ability of Q2H1 strain to solubilize phosphate under in vitro conditions. It is revealed that genes in the Q2H1 genome associated with nitrogen fixation belonged to three groups, including nitrogen fixation (nifU, sufU, salA, and nifS), nitrogen metabolism (nirA, nrtB, nasA), and glutamate synthesis (glnA, gltB, gltD, gudB), supported by evidence that Q2H1 grew on medium without nitrogen. We have also identified a siderophore gene cluster located on the chromosome of Q2H1, including seven genes (rbsR, rhbf, rhbE, rhbD, rhbC, rhbA, ddc, and an unknown gene). In the in vitro assay, a prominent brown circle around the colony was produced on the chrome azurol S medium at 48 h and 72 h post inoculation, indicating that the siderophore gene cluster in Q2H1 harbored the ability to produce siderophores. These findings imply that identifying strain-specific genes for their metabolic pathways in bacterial endophytes may reveal a variety of significant functions of plant growth-promoting mechanisms.